Estimating Tax Agency Efficiency. (26th August 2014) - Alm, James; Duncan, Denvil
<x xml:space="preserve">Abstract</x> A key variable of interest to policy makers is the efficiency with which a tax agency's production process works. Until recently, the absence of comparable data across countries on tax administration has made the comparative analysis of tax agencies impossible. The recent compilation of data by the Organisation of Economic Co‐operation and Development on administrative performance across countries has now provided this information. This article uses these data for the years 2007–2011, together with a novel three‐step estimation strategy that utilizes data envelopment analysis (DEA) and stochastic frontier analysis (SFA), to determine the relative efficiency of tax agencies in their use of inputs. Our third stage results indicate that 13 of the 28 countries in our sample are relatively efficient at collecting any of the three types of tax revenues (personal income, corporate income, and value‐added taxes). Overall, the average efficiency scores indicate that countries should be able to collect their current level of revenues with approximately 10–16 percent less inputs.